Laser Therapy for Infected Sites and Immediate Dental Implants in the Esthetic Zone: A Case Report and Review of Literature. (9th January 2020) - Crippa, Rolando; Aiuto, Riccardo; Dioguardi, Mario; Peñarrocha-Diago, María; Peñarrocha-Diago, Miguel; Angiero, Francesca
Abstract : Placement of postextraction dental implants has become a common practice. Here, we reviewed current literature, along with clinical procedures, outcomes, and incidence of complications, associated with immediate implants in infected postextraction sites. The YSGG (yttrium, scandium, gallium, and garnet) laser can significantly reduce the bacterial concentration after extracting a compromised tooth. We treated a 40-year-old woman with a compromised tooth in the esthetic zone, presenting clinical and radiological signs of infection, particularly a periapical periodontitis. The tooth was extracted after administering local anesthesia using Optocain® (mepivacaine and adrenalin 1 : 100, 000), following which the site was treated with an ErCr : YSGG (erbium, chromium-doped yttrium, scandium, gallium, and garnet) 2780 nm laser device (Biolase iPlus®). The implant (Straumann® fixture) was inserted with minimum 35 N torque, 1 mm below the most apical bone peak. Bio-Oss® and resorbable membrane were applied to improve bone healing. The use of ErCr : YSGG laser has ensured success of implant therapy performed on an infected site. There were no complications such as peri-implantitis or loss of peri-implant bone. The implant achieved good primary stability, immediate placement into an infected site did not increase complications, and the 5-year follow-up confirmed the treatment success.